Collastoma esotericum (Neodalyellida: Umagillidae), a new species of sipunculan-inhabiting rhabdocoel from Queensland, Australia - Huston, Daniel C. (Zootaxa, 2019)
The Umagillidae Wahl, represent a group of endosymbiotic Platyhelminthes which inhabit two disparate invertebrate host groups, the echinoderms and sipunculans. Sipunculan-inhabiting umagillids are morphologically distinct from those inhabiting echinoderms and have traditionally been placed in a distinct genus and subfamily, Collastoma Dörler, and the Collastominae Wahl, respectively. Although molecular data are available for umagillid species inhabiting echinoids and holothurians, species inhabiting sipunculans have yet to be evaluated with molecular data. Collastoma esotericum n. sp. from the sipunculan Phascolosoma scolops (Selenka & de Man) collected in Moreton Bay, southeast Queensland, Australia, is described. Phylogenetic analyses based on 18S rRNA gene sequences placed C. esotericum in a clade with species of the Umagillidae and the Provorticinae Luther, with strong support. However, within this clade the relationship of C. esotericum to the Umagillidae and Provorticinae was not resolved.